Differentials of Fertility in the Republic of Macedonia (empirical research) - Dragovikj, Anica (New Balkan Politics, 2001)
At the time of the last Census (1994) in the Republic of Macedonia, fertility had reached the level of 2.2 births per woman and an annual rate of population increase 1.01%. After that, TFR had been declining, and showed 1.9 children per woman in 1998. This number indicates Macedonian position in the group of countries where fertility is below the level of replacement. The reasons for such a situation are complex - cultural, demographic, economic and health-related factors. At the same time it is not possible to ignore current transitional position of the Republic of Macedonia: transit to the market economy and pluralistic political system. The reasons have not been completely clarified yet, but we can mention several reasons for the decreasing number of live births. We could point out the ageing of the fertile contingent, the insufficient financial security, the small homes etc. Essential factors are the rate of unemployment of women and their position in the family and society. At the same time, the subsequent decline in the birth rate has been also due to diminishment in the effectiveness of the state's demographic pro-natalistic policy in the country. The purpose of this survey is to state general fertility in the Republic of Macedonia using measures for current fertility and cumulative fertility and also to emphasize some differentials of fertility.
https://www.newbalkanpolitics.org.mk/item/Differentials-of-Fertility-in-the-Republic-of-Macedonia-(empirical-research)
Keywords: fertility, Macedonia, Census